The admissibility of encumbering perpetual usufruct with transmission easement - Antoniuk, Jarosław R. (The Opole Studies in Administration and Law, 2017)
The article is an analysis of the issue of admissibility of encumbering the right of perpetual usufruct of land with transmission line easement. The analysis of the existing judiciary and doctrine in this matter, conducted in the article, as well as the current regulations lead the author to the conclusion that pursuant to applicable law there are no grounds for encumbering perpetual usufruct with transmission line easement due to the binding principle of numerus clausus of encumbering rights with limited proprietary rights, with the exception of the situation of encumbering perpetual usufruct, together with buildings and facilities on the leased land which is the property of the perpetual lessee, with transmission easement. At the same time, noticing the lack of regulation of the issue by the legislator, the author considers possible solutions, which leads him to the conclusion that the legislator should expressly have indicated in the act whether transmission easement should encumber merely the right of perpetual usufruct of land or also the property leased for perpetual usufruct, which, in the opinion of the author, is a more accurate solution.